Speech Function and Process in Fake News - Dian Zelina Fitriyani; Eddy Setia; Masdiana Lubis (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
This paper deals with speech function and process found in the fake news in social media Twitter. The data used in this research are 66 clauses in the tweets about political sessions updated by the Twitter account @makLambeTurah and analysed qualitatively by applying Systemic Functional Linguistics theory. The result of the analysis shows that the most dominant speech function found in the fake news in the social media is the â€œstatementâ€ with relational process as the highest appearance. It means that the fake news writer, as the support team of the candidate, uses â€œstatementâ€ in sharing ideas, information, and issues to the readers and expects the readers to receive them, and also persuades the readers to believe and change their mind. The result also reveals that such speech function and process happen due to the relational status between the fake news writer and the candidates (politicians) he supports, that is PDIP, and the context of situation, that is in the Regional Election 2018.